The Experience of an Italian Public Homeopathy Clinic during the COVID-19 Epidemic, March–May 2020 - Rossi, Elio Giovanni (Homeopathy, 2020)
During the COVID-19 epidemic in Italy, hospital outpatient clinics progressively decreased their activities; in March 2020 they were closed except for emergencies. During this period, the activities of the public Homeopathy Outpatient Clinic of Lucca aimed at guaranteeing therapeutic continuity to patients by means of telephone or video consultations, and searching for homeopathic medicines that best responded to early COVID-19 symptoms. In March 2020, the Complementary Medicine Working Group participated in the organization of a mission of COVID-19 Chinese experts for the online training of professionals working in the Tuscan Healthcare System. The medical staff of the Lucca Clinic also cooperated in telephone health surveillance of infected patients at home, seroprevalence investigations using the capillary blood rapid test, and the implementation of the CLIFICOL (Clinical Files Collection) project.